Concise guide to workplace safety and health what you need to know, when you need it - Chambers, Gary (CRC Press, 2011)
"Going beyond compliance, this book addresses 34 major occupational safety and health topics. Organized for quick access to regulatory requirements or online resources, the text addresses required documentation, training elements, record-keeping, and more, including quality online links for background and training information and those that lead to sample programs.This is a valuable reference for business owners, HR managers, safety supervisors. lawyers, and students as well as OSHA-concerned personnel who are seeeking to be safe as well as compliant"-- Provided by publisher.
Keywords: Industrial safety.; elektronické knihy; electronic books